Pengaruh Penempatan Kerja dan Beban Kerja Terhadap Kinerja Pegawai - Praditha, Safana Mahenicha; Swasti, Ika Korika (Akuisisi : Jurnal Akuntansi, 2023)
The purpose of this study was to determine how the work environment and workload affect employee performance. Employees of PT. Wasa Mitra Engineering Area Surabaya, which was launched with 102 employees, became the population of this study. The sampling technique used the saturated Random Sampling, so that 81 employees of the field were designated as research responden. Respondents were given a questionnaire using an ordinal scale on a Likert scale, with scores ranging from 1 to 5, to collect data. Then by using partial least squares (PLS) data analysis technique, the data was processed by validity testing, reliability testing, structural model testing, and hypothesis testing. The results showed that the work placement of employees at PT. Wasa Mitra Engineering Area Surabaya has a direct and significant influence on employee performance. In addition, workload significantly and beneficially affects employee performance directly